Dignidade humana e o conceito constitucional de família: o reconhecimento dos efeitos jurídicos das uniões poliafetivas - Ribeiro, Ana Flávia Souto (2021)
The present dissertation analyzes polyamory, regarding the formation of a polyaffective family, identifying its peculiarities and problems faced when diverging from the monogamous family model. Therefore, the deductive and comparative procedural method will be used to demonstrate that polyaffective families coexist in society and in the legal system alongside monogamous families. Furthermore, it is intended to demonstrate the possibility of effects arising from the formation of polyaffective families through the constitutional principles applied to the law of families, whether by common-law marriage or marriage, using as an initial basis the understanding of the indivisibility of the legal system, by systematic interpretation of the doctrine of constitutional civil law, permeated by the application of proportionality.